ANALISIS FAKTOR YANG MEMPENGARUHI TENTANG STUNTING PADA ANAK DI KABUPATEN SIMALUNGUN TAHUN 2018 - Manurung, Evalina (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Puskesmas is a community first aid center. Therefore the Puskesmas was established in the community. Utilization of health services is the process of interaction or relationship between consumers who use services and health service providers. The service process provided starts from the registration stage until the patient gets treatment and healing. This study aims to determine the relationship of facilities and infrastructure, human resources, and distance with the utilization of health services at Bah Bolon Health Center, Simalungun Regency in 2019. This type of research uses analytic descriptive with cross sectional approach with sampling technique using Non Probability Sampling with Accidental Sampling technique. The number of samples in this study were 77 respondents namely Patients who used the Bah Bolon Puskesmas Service. Data were obtained using a questionnaire then in the data analysis using logistic regression test. Based on the analysis of the logistic regression test the most dominant variable associated with the low utilization of health services at the Bah Bolon Health Center is Facilities and Infrastructure the value of p = 0.037 and OR = 3.205. It can be concluded that incomplete Facilities and Infrastructure is a factor in the low utilization of services at the Bah Bolon Health Center in Simalungun District, which is 3,205 times more influential than the Puskesmas with complete facilities and infrastructure.